Endonezya siyasetinde kadınların temsili - Abbas, Rusdı Jusuf (My University, 2017)
Bir ülkede siyaset sistemi ve kadınların varlığı arasındaki ilişkiler çok güçlüdür. Demokratik ülkelerin genel niteliği, kadın ve erkekler de dahil ülkedeki tüm unsurlar arasında eşitliğin garanti altına alınmasıdır. Bu anlamda eşitlik, bir ülkedeki kadınlar ve erkekler arasında kamusal yaşamda ve özellikle siyasette (parlamentoda) niteliksel ve niceliksel bir dengenin bulunmasıdır. Parlamentoda hem nicelik hem de nitelik olarak kadın ve erkeklerin eşit temsili doğal bir olay değildir. Kadınlar ve erkeklerin siyasal yaşama farklı bir biçimde başlamaları siyasal alandaki deneyimlerinin eşit görülmemesine neden olmaktadır. Kadınların siyasi mücadelelere parlamentoda başlarken, erkekler siyasete parlamento dışında başlarlar. Bunun sonucunda, kadınların erkeklerin gerisinde kalmalarını düzeltmek amacıyla kadınlara kamu ve siyaset alanlarında (parlamento) bir yer edinebilmelerine yardımcı olacak mekanizmalar bulunması gerekir. Bu amaçla, kadınlaryasette önemini destekleyen hukuki araçlar ve genel seçim mekanizmaları geliştirmekle işe başlanabilir. Bu konuda önemli araçlardan bir tanesi olan genel seçimler adil ve kadınların önemini destekler ise, kadınların parlamentoda temsil edilmesiyaygınlaşabilir. Bununla birlikte, adil ve kadınların önemini destekleyen genel seçim sistemi tek başına kadınların parlamentodaki temsilini artıramaz. Bu konuda, kadınların kamu ve siyaset sektörlerinde bir yer edinmelerine sağlayacak, örneğin istek, yaratıcılık ve eğitim düzeyi gibi diğer unsurları da dikkate almamız gerekir

The existence of women in one country, has a strong relations with the political system in that country too. In the democratic countries, there is general characteristic, where they have equivalence guarantee for all of the element of the country include equivalence between women and men. The equivalence between women and men can define as balance of qualities and quantities in the public sector especially for political sector (parliament) that women and men should have. The equivalence of representation of women and men in parliament, as qualities and quantities, couldn’t happen naturally. Political experiences between women and men couldn’t been seen equally, because they have a different starting point in politics. We may say that women has been beginning their hassle from the inside house, but men has been beginning their hassle from the outside house. Because of that, we have to make the exact mechanism for women to solve their fact of having the fallen behind, in the aim for getting good position in public sector and political sector (parliament). We can start it, from creating law instruments and general election mechanisms that take sides of women importance. General election is the important instrument, because if general election system has fairness and take sides of women importance, then chance of woman to take the position in parliament will opened widely. But, the existence of the general election system that is fair and take sides of women importance can’t increase women representation in parliament directly. We think about other factors, such as the ability of women themselves, like willingness, creativity, and level of their education, for getting positions in public sector and political sector (parliament).
Keywords: Endonezya; Genel Seçim; General Election; Kadın Politic; Kadınlar; Representative; Siyaset; Siyaset ve yönetim; Temsili; Woman